PENINGKATAN HASIL BELAJAR IPA MELALUI PENGGUNAAN MEDIA GAMBAR PADA SISWA KELAS VII SMPN 1 SINABOI SATU ATAP TAHUN PELAJARAN 2015/2016 - Suwardi '; Evi Suryawati; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Teachers as implementers in schools are also required to always improve its ability in mastering and delivering lessons on students, achievement of goals in the process of learning will be seen from the student's own learning. From observations carried out at 228 1 Sinaboi one roof seen from the value of the KKM is still low at minimum ketuntasan criterion number 67.8 expected is 75. The low value of the KKM is because in the process of learning the IPA students learn independently, there is no cooperation among students, students of low motivation, lack of activity and participation of students in learning. To overcome these problems, efforts are being made is with the use of media images and engaging students actively in order to master the subject matter so that the results of the study Class VII 1 SMP Sinaboi one roof would be better. This research was conducted in Class VII 1 SMP Sinaboi one stop academic year 2015/2016 to know improvements learn IPA students using media images. This research is a research action class is done in two cycles, which consists of planning, implementation, observation and reflection. The data collected in this research is the result of student learning that consists of absorption, ketuntasan learning, student activities and teacher activities. The data collected using the test and the observation sheet. The results showed the results of students consisting of absorbance, ketuntasan learning, group learning activities, students and teacher experience increased activity. Absorption cycle I namely 70.6 (less) increased in cycle II, namely 85 (good), ketuntasan student learning on a cycle I i.e. 44% (category has been completed) improved in cycle II increased 96% (category has been completed), the learning activities of students in cycle I, i.e., 70.44% (category less), increase in cycle II, namely 87.5% (category is very good), the activity of the teacher in the cycle I namely 87.3% (category) , an increase in cycle II, namely 91.67% (category is very good). It can be concluded that the use of media images can improve learning outcomes grade VII IPA SMP 1 Sinaboi one stop Lessons Year 2015/2016.Key words: improved Learning Results, Media, Pictures